Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s11255-013-0533-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tumor size on outcomes in patients with upper urinary tract urothelial carcinoma

Abstract: Tumor size >3 cm was associated with a lower 5-year CSS at Kaplan-Meier analysis, but was not an independent predictor of CSS, bladder-only recurrence, and any recurrence-free survival at multivariable analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 21 publications
3
27
1
Order By: Relevance
“…A recent study confirmed that the tumor size was an independent predictor for worse CSS and overall survival [15]. However, in our research, after adjusting for clinicopathologic variables, the impact of tumor size on CSS was not statistically significant by multivariate analysis, in accordance with Milenkovic-Petronic's study [10]. …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A recent study confirmed that the tumor size was an independent predictor for worse CSS and overall survival [15]. However, in our research, after adjusting for clinicopathologic variables, the impact of tumor size on CSS was not statistically significant by multivariate analysis, in accordance with Milenkovic-Petronic's study [10]. …”
Section: Discussionsupporting
confidence: 87%
“…In this study, we recognized smaller tumor size (≤3 cm) as an adverse predictor of subsequent IVR in univariate analysis which was not in accordance with several previous studies [1012, 15, 18]. Our previous study [18] and that of Milenkovic-Petronic et al [10] showed that tumor size was not able to predict IVR up on univariate and multivariate analysis when tumor sizes of 5 cm and 3 cm were set as the cut-off value, respectively. Pieras et al [12] and Espiritu et al [11] confirmed that patients with a tumor size >4 cm or ≥3 cm had a higher rate of IVR.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The present results suggest that tumour size, an objective variable that can be easily measured but has been neglected for a long time, is an important prognostic factor for UTUC treated with RNU. In newly updated guidelines for UTUC , tumour size has been included for the first time as an important preoperative risk factor, based on its impact on survival outcomes; however, no solid evidence has been available to support this, with the exception of a few studies with small sample sizes and indefinite conclusions . The present results, in a multicentre and large sample size setting, represent important new evidence.…”
Section: Discussionmentioning
confidence: 75%
“…It originates exclusively from the urothelium and may occur in the lower urinary tract (bladder and urethra) or the upper urinary tract (renal pelvis and ureter) (1,2). Bladder cancer (BC) is the most common type of UC, whereas upper urinary tract urothelial carcinoma (UTUC) is relatively uncommon and accounts for only 5-10% of all UCs (3).…”
Section: Introductionmentioning
confidence: 99%